Effect of wet milling on the adsorption capacity of a greek natural zeolite used for the removal of heavy metals from solutions - Katsimicha, D.; Pentari, D.; Pantelaki, O.; Komnitsas, K. (Bulletin of the Geological Society of Greece, 2013)
The aim of the present work is the investigation of the effect of wet milling on the adsorption capacity of a Greek natural zeolite to remove heavy metal ions from solutions. The ultimate objective is to explore the potential of producing and using fine- grained zeolite in industrial and environmental applications. For this, a rich in clinoptilolite natural zeolite, was subjected to wet milling and 3 fractions were obtained (<10 μm, 10-63 μm, and 63-200 μm). The mineralogy of each fraction was determined through powder XRD and XRF analyses, while their particle size distribution and specific surface area were determined using the Laser Beam Diffraction Technique and the BET method respectively. The adsorption of Cu2+, Ni2+, Mn2+ and Cd2+ ions by each zeolite fraction was investigated using different initial metal ion concentrations (10 and 100 mg/L) and contact times (up to 72 h). The concentration of the adsorbent was kept constant (5 g/L), whereas no pH adjustment took place. The experimental results proved that wet grinding can result in the production of very fine natural zeolite (d50= 4.37 μm) without any loss of crystallinity and that this fraction exhibits substantial metal ion adsorption capacity. Adsorption is best described by the Freundlich isotherm.